Habituasi Literasi Dasar untuk Meningkatkan Minat Baca Siswa Sekolah Dasar - Ayyu Lailuki Azma; Ahmad Nurefendi Fradana (JPDI (Jurnal Pendidikan Dasar Indonesia), 2025)
This study aims to obtain information related to the implementation of the School Literacy Movement (GLS) at SD Muhammadiyah 1 Krian, Krian District, Sidoarjo Regency. The ability to understand reading plays an important role for students in obtaining and processing information, sharpening their intellect, and enriching their insights. Therefore, the habituation of literacy activities needs to be applied early to students. This study used a qualitative approach with participants consisting of 1 homeroom teacher and 10 grade 5 students. Data collection techniques were conducted through observation, in-depth interviews and documentation. The collected data were analyzed using thematic analysis techniques to identify patterns and themes that emerged from the interviews and observations. The results showed that the implementation of literacy habituation in the school runs quite well through routine reading activities before learning, the provision of reading corners in the classroom, and the active involvement of teachers and students in literacy activities. However, some obstacles were found, such as the lack of parental involvement in supporting literacy activities at home and the limited availability of varied reading materials. The school continues to develop a more effective and sustainable literacy program to support an improved literacy culture in the school environment.